Ba3B10O17F2·0.1KF: the first mixed alkali/alkaline-earth metal fluorooxoborate with unprecedented double-layered B–O/F anionic arrangement. Issue 61 (8th July 2019) - Li, Yahui; Yu, Hongwei; Han, Guopeng; Li, Hao; Yang, Zhihua; Pan, Shilie
Abstract : The first mixed alkali/alkaline-earth metal fluorooxoborate Ba3 B10 O17 F2 ·0.1KF with a unique double-layered B–O/F anionic framework was successfully synthesized and systemically characterized. Abstract : The diverse oxyfluoride species and vast number of different topological arrangements lead to fluorooxoborates' structural beauty and richness. Herein, the first mixed alkali/alkaline-earth metal fluorooxoborate Ba3 B10 O17 F2 ·0.1KF was successfully synthesized and systemically characterized. Its most important structural feature is an unprecedented double-layered B–O/F anionic arrangement.